Tracing individual experiences to systemic challenges: the (re)production of GBV in migrant women’s experiences in Canada - Busra Yalcinoz-Ucan; Evangelia Tastsoglou; Evangelia Tastsoglou; Myrna Dawson (Frontiers in Sociology)
This study examines the experiences of migrant women survivors of gender-based violence (GBV) in Canada, focusing on their processes of disclosing violence and seeking help. It explores a range of migration-related factors and circumstances that shape migrant women’s responses to violence while also aiming to reveal how migration contexts determine system-and structural-level responses to GBV, which are then traced back to women’s individual experiences and responses. Based on 17 in-depth interviews with migrant women and using a situated intersectionality perspective, our findings demonstrate first how GBV in migration is uniquely shaped and (re)produced by precarity, rooted in structural, socioeconomic, and legal conditions that translate into heightened vulnerability at the individual level. We showed that migration contexts increased women’s vulnerability to GBV, as perpetrators exploited precarity to manipulate and control women, illustrating the continuum of precarity-GBV. Secondly, this manipulation, controlling behaviors, and abuse of migrant women by perpetrators are enabled by migration policies and practices that give rise to their precarity. Additionally, our participants reported a lack of supportive social networks, which, in combination with the fear of cultural stigmatization, created a double bind hindering their processes of seeking safety. Furthermore, systemic responses to migrant women experiencing GBV were found to be inadequate, with discriminatory and negligent attitudes in healthcare, police, and legal systems. This is the continuum of systemic-individual level violence. Our findings enhance both the theoretical and empirical understanding of the continuum (i) between precarity and GBV and (ii) between systemic and individual forms of GBV in migration contexts, where precarity exacerbates GBV, and vice versa, creating a vicious cycle that deepens individual experiences of vulnerability, while the systemic and structural forms of violence contribute/(re)produce individual experiences of GBV.